TEACHING FOOD VOCABULARY TO (YOUNG LEARNERS) THROUGH INTERACTIVE ACTIVITIES - Qosimova Saida Umidjon qizi; Gaziyeva Saida (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstact Early vocabulary acquisition is crucial to language learning, particularly for young students who are still developing their linguistic and cognitive abilities. Food- related vocabulary is perfect for early vocabulary education since it is particularly relevant to children’s everyday lives and is also simpler to visualise and contextualise. In this study, children ages 4 to 7 in a kindergarten setting will be taught food terminology through interactive activities, including games, songs, role-plays, visual aids, and physical reaction tasks. Using a qualitative classroom-based methodology, the study involves 15 preschoolers over a four-week period. Every week, students encountered a range of interactive exercises created especially to teach a certain group of vocabulary words related to food. Informal learner feedback, vocabulary checklists, and instructor observations were used to gather data. The results showed that interactive exercises greatly improved learner motivation, pronunciation accuracy, and vocabulary retention. Compared to typical rote-learning approaches, children showed improved memory, more confidence in utilising new terms, and more active engagement in classes. According to the study’s findings, interactive teaching techniques are very successful and ought to be incorporated into early language education programs on a regular basis. For ESL teachers, curriculum designers, and educators working with young learners, this research offers insightful information and useful tactics for improving the effectiveness, engagement, and meaning of language learning.